Effects of Different Tillage Measures Combined with Straw Returning on Soil Enzyme Activity and Microbial Community Structure and Diversity - Sa Xiao; Bing Li; Tingting Zhang; Jianzhu Luo; Jie Wang; Xiangqian Zhang; Juan Li; Dejian Zhang (Agriculture)
Aiming at the problems of serious soil desertification, increased soil and water loss, and reduced soil-available nutrients in the agro-pastoral ecotone in Northeast Inner Mongolia, this study took corn variety A6565 as the planting crop and analyzed seven different tillage measures, deep tillage, deep loosening, shallow tillage, rotary tillage, heavy harrow, no-tillage, and control, combined with straw returning at an experimental field in Arong Banner. The analysis results are as follows: the urease activity and microbial biomass nitrogen content of the tillage method combined with straw-returning treatment were higher than other treatments. Compared with the seedling stage, the alpha diversity index of bacteria increased in the harvest stage, while that of fungi was the opposite. β diversity comparison showed that sampling time was the main factor affecting the bacterial community and composition. It was found that the dominant bacteria were Proteobacteria and Actinomycetes, and the dominant fungus was Ascomycetes. Conservation tillage combined with straw-returning treatment has a positive impact on soil microbial diversity, which is more helpful for improving soil-available nutrients and soil quality. All the findings in this study may contribute to restricting a series of important factors affecting sustainable agricultural development, such as soil degradation.